Effect of chronic exercise in healthy young male adults: a metabolomic analysis. Issue 2 (1st April 2020) - Koay, Yen Chin; Stanton, Kelly; Kienzle, Vivian; Li, Mengbo; Yang, Jean; Celermajer, David S; O'Sullivan, John F
Abstract: Aims: To examine the metabolic adaptation to an 80-day exercise intervention in healthy young male adults where lifestyle factors such as diet, sleep, and physical activities are controlled. Methods and results: This study involved cross-sectional analysis before and after an 80-day aerobic and strength exercise intervention in 52 young, adult, male, newly enlisted soldiers in 2015. Plasma metabolomic analyses were performed using liquid chromatography, tandem mass spectrometry. Data analyses were performed between March and August 2019. We analysed changes in metabolomic profiles at the end of an 80-day exercise intervention compared to baseline, and the association of metabolite changes with changes in clinical parameters. Global metabolism was dramatically shifted after the exercise training programme. Fatty acids and ketone body substrates, key fuels used by exercising muscle, were dramatically decreased in plasma in response to increased aerobic fitness. There were highly significant changes across many classes of metabolic substrates including lipids, ketone bodies, arginine metabolites, endocannabinoids, nucleotides, markers of proteolysis, products of fatty acid oxidation, microbiome-derived metabolites, markers of redox stress, and substrates of coagulation. For statistical analyses, a paired t -test was used and Bonferroni-adjusted P -value of <0.0004 was considered to be statistically significant. The metabolite dimethylguanidino valeric acid (DMGV) (recently shown to predict lack of metabolic response to exercise) tracked maladaptive metabolic changes to exercise; those with increases in DMGV levels had increases in several cardiovascular risk factors; changes in DMGV levels were significantly positively correlated with increases in body fat ( P = 0.049), total and LDL cholesterol ( P = 0.003 and P = 0.007), and systolic blood pressure ( P = 0.006). This study was approved by the Departments of Defence and Veterans' Affairs Human Research Ethics Committee and written informed consent was obtained from each subject. Conclusion: For the first time, the true magnitude and extent of metabolic adaptation to chronic exercise training are revealed in this carefully designed study, which can be leveraged for novel therapeutic strategies in cardiometabolic disease. Extending the recent report of DMGV's predictive utility in sedentary, overweight individuals, we found that it is also a useful marker of poor metabolic response to exercise in young, healthy, fit males.